Job Challenge Profile Facilitator's Guide - McCauley, Cynthia D.; Ohlott, Patricia J.; Ruderman, Marian N. (Center for Creative Leadership, 2015)
The Center for Creative Leadership has found that successful managers acquire many core skills from their work assignments. Although, job assignments are a rich source of learning, some assignments provide more of a learning opportunity than others. Leaders will use their feedback from the JCP to assist them in learning from handling unfamiliar tasks, driving workplace transformation, seeking additional responsibilities, dealing with external pressure, managing group diversity-and much more! The Facilitator's Guide details the essential workshop procedures (including assessment setup, administration, and follow-up). You don't need to be a training professional to use this tool in your organization: this guide gives you all the basics. Your participants will be able to quickly score and interpret the assessment using the practical Participant Workbook. With the aid of this guide, they will determine what and how much they are learning, what parts of their jobs hold key challenges, and what strategies they might adopt to derive maximal learning from these experiences. Enable your employees to thrive on challenge! With the assistance of a world-renowned leadership authority, you will foster job satisfaction organization-wide.